Bagaimana Media Sosial dan Ekuitas Merek dapat Meningkatkan Minat Beli Produk Kopi Kenangan? - Arnu, Anggi Pasca; Gaffar , Vanessa; Arief , Meta (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2025)
Research aim : This study investigates the influence of social media marketing and brand equity on consumer purchase intention toward Kopi Kenangan, a leading Indonesian coffee brand and the first New Retail F&B Unicorn in Southeast Asia. Approach : A quantitative descriptive approach was employed, collecting data from 400 Kopi Kenangan Instagram followers. Multiple linear regression analysis was used to assess both partial and simultaneous effects of social media marketing and brand equity on purchase intention. Research Finding: The results show that social media marketing has a positive partial effect on purchase intention, while brand equity demonstrates a stronger partial . When analyzed simultaneously, both variables explain confirming a significant combined impact. Theoretical contribution/Originality : This research enriches existing literature by emphasizing the role of social media marketing and brand equity in shaping consumer behavior in the digital era. Practitioner/Policy implication : The findings suggest that F&B businesses should strengthen their brand equity and leverage social media marketing strategies Research limitation :. he study focuses solely on followers of a single brand’s social media platform, which may limit the generalizability of results across other consumer groups or industries.